DYE-SENSITIZED SOLAR CELLS WITH A SOLID HOLE CONDUCTOR - DENG, LULU (My University, 2012)
Dye-sensitized Solar Cells (DSSCs) with liquid electrolyte lack long term stability because of volatility of the electrolyte and assembly problems. Replacement of the volatile liquid-state electrolyte with solid-state hole conductor thus becomes necessary. A small molecule based hole conductor, Copper Phthalocyanine (CuPc), is proposed here to replace the liquid electrolyte, for its intrinsic thermal and chemical stabilities. However, a lower short circuit current was found in the CuPc solid state device from I-V curve, which is closely related to the inefficient hole transport in the CuPc thin film. Therefore, Two-Dimensional Grazing Incidence X-ray Diffraction (2D GIXRD) is utilized to study the phase and texture of CuPc thin film. It is found that the CuPc thin film has a cystallinity of greater than 80%, which is good for hole conducting. However, the β-phase formation lowers the overall hole conductivity. The hole conductivity of β-phase CuPc is two orders of magnitude smaller than that of α-phase CuPc, due to a less overlap in the π-π stacking. As a result, the low hole conductivity of β-phase CuPc is the reason that leads to an inefficient hole transport and reduces the short-circuit current of the solid-state DSSC. Therefore, future work will be necessary to isolate α-phase CuPc, in order to be successfully applied into the solid-state DSSCs.
Keywords: Dye-sensitized Solar Cells; Polymer and Organic Materials; Semiconductor and Optical Materials; Polymer and Organic Materials